A lateral flow dipstick combined with reverse transcription recombinase polymerase amplification for rapid and visual detection of the bovine respirovirus 3 - Zhao, Guimin (Mol Cell Probes, 2018)
Bovine respirovirus 3 also known as Bovine parainfluenza virus type 3 (BPIV3) is one of the most important viral respiratory agents of both young and adult cattle. Rapid diagnosis could contribute greatly in containing epidemics and thus avoid economic losses. However, the lack of robust isothermal visual method poses difficulty. In this study, a novel isothermal assay for detecting BPIV3 was established. The method includes a lateral flow dipstick (LFD) assay combined with reverse transcription recombinase polymerase amplification (RT-RPA). First, the analytical sensitivity and specificity of BPIV3 LFD RT-RPA were tested. The LFD RT-RPA assay has a detection limit of up to 100 copies per reaction in 30 min at 38 °C. Then the performance of LFD RT-RPA was evaluated using 95 clinical samples. Compared to qPCR, the LFD RT-RPA assay showed a clinical sensitivity of 94.74%, a clinical specificity of 96.05% and 0.8734 kappa coefficient. These results have demonstrated the efficiency and effectiveness of the method to be developed into a point of care protocol for the diagnosis of BPIV3.